2013
DOI: 10.1002/zaac.201300030
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Ionic Liquids Containing the ­[Al(OC6H4CN)4] Anion

Abstract: The synthesis, structure, and physical properties of ionic liquids (IL) bearing the novel [Al(O–C6H4–CN)4]– ion as counterion to the commonly used [NR4]+, [PR4]+ and imidazolium ions are reported. Both the influence of the alkyl chain length as well as the functionalization with cyano groups is studied. These ILs are easily obtained by reaction of Ag[Al(O–C6H4–CN)4] with the corresponding ammonium, phosphonium, and imidazolium halides. The stability towards electrophilic cations was investigated. All prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Generally, the shift to lower wave numbers (ca. 2220 cm –1 ) indicates a decrease of interionic interaction by the CN group as shown for [Al(O–C 6 H 4 –CN) 4 ] – containing salts of organic cations 35. In turn, the coordination of a Lewis acid to a NC– R species causes a significant band shift to higher wave numbers {cf.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…Generally, the shift to lower wave numbers (ca. 2220 cm –1 ) indicates a decrease of interionic interaction by the CN group as shown for [Al(O–C 6 H 4 –CN) 4 ] – containing salts of organic cations 35. In turn, the coordination of a Lewis acid to a NC– R species causes a significant band shift to higher wave numbers {cf.…”
Section: Resultsmentioning
confidence: 78%
“…This kind of interaction was already discussed in [Al(O–C 6 H 4 –CN) 4 ] – ‐based ionic liquids, for which similar structural features were described [cf. C ··· O 3.367(2) Å] 35. The overall assembly, formed by these C–H ··· O‐contacts, is shown in Figure 7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Finze et al [17] reported more efficient syntheses of M[BF(CN) 3 ] (M = Na, K) with Me 3 SiCl as a catalyst independently to our work on catalyzed F -/CNsubstitution reactions. [18][19][20][21][22][23][24] Cyanidoborate salts are used widely, [25][26][27][28][29] for example, as starting materials for light-element ceramics, [30] the generation of 3D coordination polymers, or as anions in ionic liquids (ILs). [8,11,13,[31][32][33] Cyanidoborate-based ILs can be obtained readily through salt metathesis reactions.…”
mentioning
confidence: 99%